The Importance of Brand Stories towards Brand Perception and Purchase Intention in Gen Z Indonesians - Fauzia Qurani Andanawarih; Grasheli Kusuma Andhini (The Winners, 2022)
The research explored the importance of brand story towards Indonesia’s Gen Z and how it affected buying decisions and perception towards the brand. It explored if creating a brand story is a central element in creating and differentiating Indonesian fashion brands that becomes a beneficial tool for both business owner and its customer. The research was conducted through an exploratory descriptive approach by using survey on Indonesian collectivist society—those who behave communally based on in-group norms including the 84 Gen Z—as well as archival research on two similar fashion brands, and interviews on one customer and one brand owner. The research findings point out that brand stories take a positive effect on a customer’s perception towards a brand and their purchase decision. While brand stories do have an influence in shaping the image of a brand as well as becoming a factor in a customer’s purchase decision process, other brand attributes such as packaging, social media content, and logos also plays an important role in a shaping brand image, as well as the customer’s final purchase decision. Furthermore, the opinions of a key opinion leader about a brand or product greatly matters in this society and that people are more willing to purchase a product if it has already been positively reviewed by a key opinion leader.